2015
DOI: 10.1016/j.renene.2015.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Isolated induction generator in a rural Brazilian area: Field performance tests

Abstract: a b s t r a c tIsolated generation in micro hydroeletric power plant (MHPP) through the induction generator (IG) has been the subject of extensive research due to the fact that this type of electrical machine is easy to operate, requires simplified maintenance, and has also a lower cost when compared to the synchronous machine, mainly in the range from 0.5 to 50 kW. In this work a single voltage control loop of an squirrel cage induction generator in an isolated operation system was implemented in a 30 kW MHPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…A PAT technology was tested with a laboratory prototype for a case study of an aqueduct in the city of Merano, Italy [14]- [15], in which the authors concluded to be possible to obtain 76% of the maximum efficiency of the turbine working in both reverse and direct mode. A pumping system of a micro-hydroelectric power plant in a rural farm in Brazil was designed with a turbine capable of performing both direct and inverse (PAT) modes coupled to a standalone isolated induction generator, considering a uniform rotational speed [16]. [12] started to analyze the global efficiency of the PATs in a laboratory prototype system.…”
Section: Introductionmentioning
confidence: 99%
“…A PAT technology was tested with a laboratory prototype for a case study of an aqueduct in the city of Merano, Italy [14]- [15], in which the authors concluded to be possible to obtain 76% of the maximum efficiency of the turbine working in both reverse and direct mode. A pumping system of a micro-hydroelectric power plant in a rural farm in Brazil was designed with a turbine capable of performing both direct and inverse (PAT) modes coupled to a standalone isolated induction generator, considering a uniform rotational speed [16]. [12] started to analyze the global efficiency of the PATs in a laboratory prototype system.…”
Section: Introductionmentioning
confidence: 99%
“…This circuit topology and its control scheme are complicated and unsuitable for low-power applications. A thyristor-based SVG can be adopted instead of the VSC-based SVG [23,36]. However, the SEIG current harmonics and large DC bus voltage 𝑣 𝐷 still cause a low system efficiency.…”
Section: Assesment Of Possible Power Conversion Topologiesmentioning
confidence: 99%
“…Small capacity IGs exhibit low reactance-to-resistance ratio and low mechanical inertia, and they present a weak source before the load. Moreover, when a weak grid caters to perturbing loads, issues such as voltage sag/swell, harmonics, unregulated frequency, and voltage collapse pose problems for power supply [5]. Investigations reported so far address only a few of the aforementioned issues, namely, the voltage regulation and harmonic compensation of self-excited induction generators (SEIGs) by employing pulse-width modulation (PWM) rectifiers and static synchronous compensator (STATCOM) [6].…”
Section: Introductionmentioning
confidence: 99%